New ideas and concepts in sport shoe development - Nigg, B. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The sport biomechanist is often challenged to test performance during competition and not in the laboratory environment. While ecological validity of data must always be of concern, measurement error (both system, and modelling) and the characteristics of equipment used (manual or automatic?), often mean that data are collected under simulated match conditions. This paper will review the vexing question of laboratory versus field testing from a biomechanical perspective. Current data suggest that for movements involving out of plane rotations, laboratory testing with an opto-reflective system (cluster based model), provides a more accurate measure of elbow angle when compared with the same angle collected with a video-based system (vector model) during a simulated cricket bowling task.